Taming TikTok: how BIPOC individuals perceive and interact with algorithmically generated content - Jiarun Dai; Naila Hajiyeva; Sehba Wani; Kayla Booth (Information Research: An International Electronic Journal)
Introduction. TikTok’s recommendation algorithm plays a crucial role in shaping user experiences, raising concerns about algorithmic bias, content suppression, and misinformation, particularly for BIPOC users. This study explores how BIPOC individuals perceive and interact with TikTok’s algorithm, focusing on content visibility, algorithmic manipulation, and experiences with problematic content.